Size-dependent chemosensitization of doxorubicin-loaded polymeric nanoparticles for malignant glioma chemotherapy. Issue 2 (20th December 2021) - Gao, Meng; Chen, Yue; Wu, Chenghu
ABSTRACT: Chemotherapy is a traditional treatment method in clinical cancer treatment. However, it is limited due to the large toxic side effects of chemotherapeutics. Nanomedicines have shown great potential in the application of tumor therapy. The size of nanoparticles as a crucial factor in the enhanced permeability and retention (EPR) effect can be regulated for the enhanced chemotherapy. Therefore, we believe that regulation of nanoparticle size can be used as an effective sensitizer to enhance the therapeutic effect of chemotherapy drugs on tumors. Here, we prepared several nanoparticles of different hydrodynamic diameters commonly found in nanomedical applications by the diblock copolymer of methoxy polyethylene glycol-poly ( ϵ ‐caprolactone) (mPEG-PCL). The blood circulation effect and organ distribution in blood were detected by fluorescence labeled nanoparticles. We found that the small-sized nanoparticles exhibited much longer blood circulation time than the large-sized nanoparticles in vivo, and thus the nanoparticle concentration in the tumor tissue was relatively high. Systematic injection of the doxorubicin (DOX) loaded nanoparticles can effectively inhibit tumor growth. Compared to the free drug, tumor cells were much more sensitive to DOX loaded nanoparticles of small size. Our nano-drug delivery system has been proven to be safe and nontoxic in vivo and was suitable for use as a sensitizer in clinical oncology chemotherapy.